2010
DOI: 10.1016/j.neuroimage.2010.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome association study of brain-wide imaging phenotypes for identifying quantitative trait loci in MCI and AD: A study of the ADNI cohort

Abstract: A genome-wide, whole brain approach to investigate genetic effects on neuroimaging phenotypes for identifying quantitative trait loci is described. The Alzheimer's Disease Neuroimaging Initiative 1.5 T MRI and genetic dataset was investigated using voxel-based morphometry (VBM) and FreeSurfer parcellation followed by genome-wide association studies (GWAS). One hundred forty-two measures of grey matter (GM) density, volume, and cortical thickness were extracted from baseline scans. GWAS, using PLINK, were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
336
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(351 citation statements)
references
References 52 publications
12
336
1
2
Order By: Relevance
“…More than 3,500 native Englishspeaking adults with normal or corrected-to-normal vision were recruited from Harvard University, MGH, and the surrounding Boston communities. To avoid spurious effects resulting from population stratification, we restricted our analyses to 1,320 young adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) Imaging Data Processing. We used FreeSurfer (freesurfer.net) (49), version 4.5.0, a freely available, widely used, and extensively validated brain MRI analysis software package, to process the structural brain MRI scans and compute global and regional morphological measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 3,500 native Englishspeaking adults with normal or corrected-to-normal vision were recruited from Harvard University, MGH, and the surrounding Boston communities. To avoid spurious effects resulting from population stratification, we restricted our analyses to 1,320 young adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) Imaging Data Processing. We used FreeSurfer (freesurfer.net) (49), version 4.5.0, a freely available, widely used, and extensively validated brain MRI analysis software package, to process the structural brain MRI scans and compute global and regional morphological measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Brain imaging data are a prototype case where a vast array of potentially relevant phenotypes are routinely collected and phenotypic complexity has grown exponentially as new tools to analyze highresolution structure and point-to-point connectivity have emerged. A wide range of volume-, surface-, and connection-based measures are of potential interest in analyzing the relationship between genetic and brain data in the context of clinical conditions (17)(18)(19)(20)(21). Although, in principle, any measure computable from different brain imaging modalities can be used as phenotypes in genetic studies, ideal candidate imaging traits should be heritable intermediate (or endo-) phenotypes (22)(23)(24), to uncover the genetic underpinnings of various neuropsychiatric disorders or biological processes of interest (25).…”
mentioning
confidence: 99%
“…A poly T repeat in an intronic polymorphism (rs10524523) (intron 6) in the TOMM40 gene, which encodes an outer mitochondrial membrane translocase involved in the transport of amyloid-β and other proteins into mitochondria, has been implicated in AD [31][32][33][34][35][36][37][38][39][40][41][42][43][44], and APOE-TOMM40 genotypes have been shown to modify disease risk and age at onset of symptoms [32][33][34][35][36][37]45], although the latter assumption needs replication due to contradictory results [36,[46][47][48][49]. A fixed-effect meta-analysis approach showed that rs4420638 at the TOMM40/APOE/APOC1 gene locus is associated with longevity [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…A poly T repeat in an intronic polymorphism (rs10524523) (intron 6) in the TOMM40 gene, which encodes an outer mitochondrial membrane translocase involved in the transport of amyloid-β and other proteins into mitochondria, has been implicated in AD [20][21][22][23][24][25][26][27][28][29][30][31][32][33], and APOE-TOMM40 genotypes have been shown to modify disease risk and age at onset of symptoms [21][22][23][24][25][26]34]. A fixed-effect meta-analysis approach showed that rs4420638 at the TOMM40/APOE/APOC1 gene locus is associated with longevity [35,36].…”
Section: Editorialmentioning
confidence: 99%